Socio-economic approach to management treatise theory and practices - Savall, Henri; Zardet, Véronique (ISEOR book series, 2023)
"This Treatise on Socio-Economic Approach to Management (SEAM) will be a major reference work for a long time to come, not only for companies but also, and more globally, for the definition of public policies and in our understanding of "living together." This treatise would not have been possible and would not have brought together so many eminent contributors without the determined and absolute commitment of Professor Henri Savall, joined by Professor Véronique Zardet, to put the human dimension at the center of economic and social activity"--